Poland’s Cultural Diplomacy in Ukraine - Halyna Lutsyshyn; Lesia Kornat; Olena Lukachuk (Language, Culture, Politics)
The article examines the peculiarities of the implementation of the Republic of Poland's implementation of cultural diplomacy in Ukraine.  Considerable attention is paid to the analysis of the basic foundations and principles of the development of Polish cultural diplomacy in modern modern times, and the activities of governmental and non-governmental institutions working in the field of cultural diplomacy. It is noted that the development of Poland's cultural diplomacy has been positively influenced by its EU membership, the modernization and expansion of cultural infrastructure, the growing number of cultural institutions in Poland, and the intensification of Ukrainian-Polish cultural cooperation The activities of cultural diplomacy actors such as the Polish Institute in Kyiv, the Center for Polish Culture and European Dialogue in Ivano-Frankivsk, the Mickiewicz Institute, the Stefan Batory Foundation, the Other Space Foundation, the Krzysztof Skubiszewski Foundation, and the Lane Kirkland Program, and their roles in developing and strengthening Ukrainian-Polish cultural cooperation are analyzed. Since the onset of Russia's full-scale invasion of Ukraine, it is noted that the Polish government has continued to advance cultural diplomacy in Ukraine. The Polish Institute, in particular, has been implementing numerous cultural and artistic projects at various levels. Support for the Polish diaspora during the war has intensified, Polish culture is being increasingly promoted, and scientific diplomacy is actively progressing, particularly through joint Ukrainian-Polish research, scientific exchanges, and academic mobility programs for scholars.